The trend in primary health care preference in China: a cohort study of 12,508 residents from 2012 to 2018 - Guangsheng Wan; Xiaolin Wei; Hui Yin; Zhiwang Qian; Tingting Wang; Lina Wang (BMC, 2021)
Abstract Background Residents' preference for primary health care (PHC) determined their utilization of PHC. This study aimed to assess the determinants of PHC service preference among the residents and the trend in PHC service preference over time in China. Methods We employed the nationally representative longitudinal data from 2012 to 2018 based on the China Family Panel Studies. The analysis framework was guided by the Andersen model of health service utilization. We included a total of 12,508 individuals who have been successfully followed up in the surveys of 2012, 2014, 2016, and 2018 without any missing data. Logistic regressions were performed to analyze potential predictors of PHC preference behavior. Results The results indicated that individuals' socio-economic circumstances and their health status factors were statistically significant determinants of PHC preference. Notably, over time, the residents' likelihood of choosing PHC service represented a decreasing trend. Compare to 2012, the likelihood of PHC service preference decreased by 18.6% (OR, 0.814; 95% CI, 0.764-0.867) in 2014, 30.0% (OR, 0.700; 95% CI, 0.657-0.745) in 2016, and 34.9% (OR, 0.651; 95% CI, 0.611-0.694) in 2018. The decrease was significantly associated with the changes in residents' health status. Conclusions The residents' likelihood of choosing PHC service represented a decreasing trend, which was contrary to the objective of China's National Health Reform in 2009. We recommend that policymakers adjust the primary service items in PHC facilities and strengthen the coordination of service between PHC institutions and higher-level hospitals.